Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 119305 species occurrences available in GBIF matching the query: { "and" : [ "Country is Mexico", "TaxonKey is Gastropoda" ] } The dataset includes 119305 records from 127 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002586-170714134226665/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences